Analisis Pengaruh Pelatihan dan Lingkungan Kerja serta Kaitannya Terhadap Peningkatan Kinerja Pegawai Kementerian Ketenagakerjaan Republik Indonesia - M. Reza; Nurvi Oktiani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Human resources have a very important role in determining the progress of an organization, the goals of an agency are largely determined by the performance of human resources or the performance of employees within it. To improve employee work performance, one way is to provide training to employees and pay attention to the work environment around employees. The aim of this research is to determine the effect of training and work environment simultaneously on the performance of employees of the Directorate General of Binalavotas. The method used in this research is a quantitative method which uses a sample of 50 respondents and the sampling in this research is a non-probability technique with census sampling, data collection was carried out using a questionnaire. The results of research using the t test show that the training variable partially has a positive and significant effect on employee performance, namely the value of T-count > T-table (8.581 > 2.012) with a significance level of 0.000 < 0.05 and the work environment variable partially has a positive and significant effect on employee performance, namely obtained T-count>T-table value (10,227 > 2,012) with a significance level of 0.000 < 0.05. The results of the F test for the training and work environment variables can be concluded that the training and work environment variables simultaneously have a positive and significant effect on employee performance, namely the value obtained Fcount>Ftable (58.725 > 3.20) with a significance level of 0.000 <0.05.